Community-based monitoring of Indigenous food security in a changing climate: Global trends and future directions - and Lam, Steven; Dodd, Warren; Skinner, Kelly; Papadopoulos, Andrew; Zivot, Chloe; Ford, James; Garcia, Patricia J.; Team, IHACC Research; Harper, Sherilee L. (Environmental Research Letters, 2019)
Climate change is expected to exacerbate existing food security challenges, especially in Indigenous communities worldwide. Community-based monitoring is considered a promising strategy to improve monitoring of, and local adaptation to climatic and environmental change. Yet, it is unclear how this approach can be applied in food security or Indigenous contexts. The objectives of this paper are to: 1) review and synthesize the published literature on community-based monitoring of Indigenous food security; and, 2) identify gaps and trends in these monitoring efforts in the context of climate change. Using a systematic search and screening process, we identified 86 published articles. To be included, articles had to be published in a journal, describe a community-based monitoring system, describe any aspect of food security, and explicitly mention an Indigenous community. Relevant articles were thematically analyzed to characterize elements of community-based monitoring in the context of climate change. Results show that the number of articles published over time was steady and increased more than two-fold within the last five years. The reviewed articles reported on monitoring mainly in North America (37%) and South America (28%). In general, monitoring was either collaborative with local communities (51%) or externally-driven (37%), and focused primarily on tracking wildlife (29%), followed by natural resources (16%), environmental change (15%), fisheries (13%), climate change (9%), or some combination of these topics (18%). This review provides an evidence-base on the uses, characteristics, and opportunities of community-based monitoring, to guide future food security monitoring efforts in the context of climate change.